Direct and Indirect Effects of Customer Engagement and Brand Trust on Loyalty Through Purchase Decisions: An Empirical Study on Fashion Product Customers in Indonesia - Oswari, Teddy (International Journal of Innovative Research and Scientific Studies, 2025)
In the last ten years, Indonesian local fashion brands have been able to compete with foreign brands, and local fashion has begun to take over the domestic fashion market share. Erigo, Bloods, Roughneck, 3Second, Sch, Eiger, Thanksinsomnia, Geoff Max, Nevada, and Vans are local fashion product clothing brands. Customer loyalty, from a marketing management perspective, plays an important strategic role in capturing market share. This research aims to analyze the effect of customer engagement and brand trust, both directly and indirectly through purchase decisions, on customer loyalty. The research analyses were based on the quantitative method. The sampling technique uses convenience sampling with a total of 150 respondents, namely consumers who use Erigo, Bloods, Eiger, and Nevada products. Data collection was conducted using a questionnaire that had been validated and proven reliable, which was distributed through social media, namely Instagram and TikTok. Partial Least Squares Structural Equation Modeling (SmartPLS-SEM) was used as software for analyzing research data. The results showed that customer engagement and brand trust affect purchase decisions. Customer engagement and purchase decisions do not affect customer loyalty. Purchase decisions mediate the effect of customer engagement and brand trust on customer loyalty. Partially, only customer engagement has an effect on customer loyalty.